Tourism, recreation and biological invasions (Wallingford, Oxfordshire; Boston, MA CABI, 2023)
"This book provides a detailed review on the role of tourism and recreation in promoting biological invasions, and how invasions may affect these activities. It reviews management options and solutions to minimize the impacts from invasive non-native species in relation to tourism. It covers diverse regions and varied invasive organisms." --
Introduction: Tourism, recreation and biological invasions / Cristobal Pizarro, Agustina Barros, Lisa Rew, Ross Shakleton, Anibal Pauchard -- Nature-based tourists as seed dispersal vectors / Catherine Pickering, Michael Ansong -- The role of roads and trails for facilitating mountain plant invasions / Agustina Barros, Sylvia Haider, Jana Müllerová, Jake M. Alexander, Maria Alisa Alvarez, Valeria Aschero, Curtis Daehler, Gwendolyn Peyre, Amanda Ratier Backes, José Ramón Arévalo, Lohengrin Cavieres, Pervaiz Dar, Eduardo Fuentes-Lillo, Rebecca Liedtke, Keith McDougall, Ann Milbau, John W. Morgan, Bridgett J. Naylor, Martín A. Nuñez, Aníbal Pauchard, Irfan Rashid, Zafar A. Reshi, Lisa Rew, Veronica Sandoya, Timothy Seipel, Tom Vorstenbosch, Michaela Vítková, Neville Walsh, Ronja E. M. Wedegärtner, Shengwei Zong Jonas J. Lembrechts -- Fungal invasions and potential spread through tourism and recreation / Sarah E. McGrath-Blaser, Ana V. Longo -- The role of human activities in the introduction of non-native plants to Antarctic and Subantarctic islands / Eduardo Fuentes-Lillo, Marely Cuba-Diaz -- Recreational fishing as a major pathway for the introduction of invasive species / Josie South, Patricia Charvet, Dumisani Khosa, Emily R. C. Smith, Darragh J. Woodford -- The role of hunting, zoos and aquaria as pathways for vertebrate invasions / Andrea Monaco, Riccardo Scalera, Lucilla Carnevali and Piero Genovesi -- Plant invasions associated with ski resorts / Keith L. McDougall, Lohengrin A. Cavieres -- The role of second homes in non-native plant invasions / Ana Novoa, Kim Canavan, Susan Canavan -- Negative impacts in tourism of yellow jackets (Vespula germanica) in wilderness areas of Chile / Claudia Cerda, Ana Araos, Iñigo Bidegain -- Costs and impacts of aquatic plant invasions for tourism and recreation / Stephanie Bradbeer, Zarah Pattison -- The impact of invasive aquatic animals on tourism and recreation / Louisa E. Wood, Kate Dey, Charlotte Clubley, Adam Kennerley, James Guilder, Emily Smith, Ewan Trégarot -- Tourists' knowledge, perceptions and behaviours toward invasive species / Ross T. Shackleton, Cristóbal J. Pizarro, Sebastian Dario Rossi -- On visitors' minds: knowledge and perceptions of invasive non-native plant species in mountains ecosystems / Sebastian D. Rossi, María Alisa Alvarez, Valeria Aschero, Muriel Hellvig, Lorena de Jesús Bonjour, Ana Mazzolari, Juan Pablo Scarpa, Agustina Barros -- Contrasting tourist attitudes toward non-native species: a case study in Yellowstone National Park, USA. / Jerry Johnson -- Complexities of deer management, recreation and hunting tourism in Northeast Victoria, Australia / Jennifer Bond -- Managing invasive species in tourist and recreation areas of Montana, USA / Lisa J. Rew, Christian Larson -- Conclusion: A summary of current knowledge and future directions on the interplay between invasive species, tourism and recreation / Ross Shakleton, Lisa Rew, Anibal Pauchard, Cristobal Pizarro, Agustina Barros.
Includes bibliographical references and index
Keywords: Barros, Agustina; Shackleton, Ross; Rew, Lisa; Pizarro, Cristóbal; Pauchard, Aníbal; Ecotourism; Nature -- Effect of human beings on ecotourism; Biological invasions .; Recreation -- Environmental aspects .; Tourism -- Environmental aspects .